Amphetamine-type stimulant use among men who have sex with men (MSM) in Vietnam: Results from a socio-ecological, community-based study. (1st January 2016) - Vu, Nga Thi Thu; Holt, Martin; Phan, Huong Thi Thu; Le, Huong Thi; La, Lan Thi; Tran, Gioi Minh; Doan, Tung Thanh; Nguyen, Trang Nhu Nguyen; de Wit, John
Highlights: Amphetamine-type stimulant (ATS) use was relatively common among men who have sex with men (MSM) from two cities in Vietnam. One fifth of recent methamphetamine users were categorized as high-risk users. Correlates of drug use included societal, community and individual-level factors. Interventions should target men involved in sex work and sexually adventurous men. Abstract: Introduction: Amphetamine-type-stimulants (ATS) use is associated with HIV-related sexual risk behaviours and is an emergent problem among men who have sex with men (MSM) in Vietnam. The purpose of this study is to describe ATS use patterns and understand the correlates of recent methamphetamine use from a socio-ecological perspective. Methods: From September through December, 2014, 622 MSM were recruited in Hanoi and Ho Chi Minh City, Vietnam. We collected information on demographic characteristics, HIV testing behaviours, use of ATS and other recreational drugs (ever and recently), sexual sensation seeking, depressive mood, experienced and internalized stigma related to homosexuality, social involvement with other MSM, and perceptions of ATS use in MSM networks. We performed descriptive statistics to describe ATS use patterns and multivariate logistic regression to establish independent correlates of recent methamphetamine use. Results: Nearly one-third (30.4%) had ever used ATS, including 23.6% who had used methamphetamine, 4.3% who had used amphetamine ('speed') and 20.9% who had used ecstasy. 20.1% and 11.9% had ever used methamphetamine and ecstasy, respectively, during sex. Eighteen percent of methamphetamine users were classified as engaged in high-risk use. Recent methamphetamine use (in the last 3 months) was associated with participants perceiving more methamphetamine use in their MSM network, recent sex work, and higher sexual sensation seeking scores. Conclusions: ATS use is relatively prevalent among MSM sampled in Vietnam's main cities. Interventions to address methamphetamine are warranted for MSM in Vietnam. Methamphetamine treatments are needed for high-risk users.